Studies on Trimethoxy Indan-1-yl-acetic Acids as Anti-hyperchlestrolemic Agents - ADAK, MANORANJAN; KUMAR GUPTA, JAYANTA (Asian Journal of Chemistry, 2010)
Trimethoxy indan derivatives having (R = alkyl group) at the α-carbon atom of acetic acid moiety were synthesized and screened for anti-hypercholesterolemic activity in male albino Charles Foster rats. It was observed that percentage yield as well as pharmacological activity of synthesized compounds decreased on increasing the α-alkyl group.